Out of Africa : Post-Structuralism's Colonial Roots. - Ahluwalia, D. P. S. (D. Pal S.) (Postcolonial politics., 2010)
Making a convincing and controversial case that post-structuralism has colonial and postcolonial roots, this title features a wide-ranging discussion, ranging across authors as different as Foucault, Derrida, Fanon, Althusser, Cixous, Bourdieu and Lyotard, that enables the reader to make connections that have remained unnoticed or been neglected.